Bank Syariah dalam Perspektif Hukum dan Prinsip Syariah Analisis atas Substansi Identitasnya - Aulia Rahmadani; Zainal Abidin; Ilham Ilham (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the legal foundation and operational principles of Islamic banking in Indonesia. The background of this research stems from the necessity of a comprehensive understanding of the legitimacy and Sharia-based principles that underpin banking activities within the Islamic financial system. This research uses a literature review method by analyzing legal documents such as Law Number 21 of 2008 and fatwas issued by the National Sharia Council of MUI, along with other academic references. The findings indicate that Islamic banking in Indonesia is built upon a strong legal framework and clear Sharia principles, such as the prohibition of usury (riba), justice, and transparency. However, there are still challenges in the practical implementation of these principles, particularly in terms of public understanding and consistent interpretation. This research is expected to serve as an initial reference for strengthening legal literacy and Sharia principles in banking, and to support the development of a more inclusive Islamic financial system.